PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), PROFITABILITAS, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Arvina karisma cahya; Krisnawuri handayani (Journal of Innovation Research and Knowledge, 2025)
This research aims to examine and analyze the influence of Corporate Social Responsibility (CSR), Profitability and Institutional Ownership on Company Value in retail companies listed on the BEI in 2019- 2023. The data collection technique uses the purposeful sampling method, which means that of the 31 retail company population, there are only 8 companies that meet the sample criteria. The statistical analysis used is descriptive analysis, classical assumption test, and multiple linear regression analysis. The results of this research are that partially CSR, Profitability and Institutional Ownership have a significant effect on company value. Simultaneously, CSR does not have a significant influence on company value in retail companies for the 2019-2023 period. Profitability has a significant influence on company value in retail companies for the 2019- 2023 period. Institutional ownership does not have a significant influence on firm value in retail companies for the 2019-2023 period